2009
DOI: 10.1007/s00192-009-1027-2
|View full text |Cite
|
Sign up to set email alerts
|

TVT and TVT-O for surgical treatment of primary stress urinary incontinence: prospective randomized trial

Abstract: The groups showed comparable objective and subjective cure rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 27 publications
2
23
0
4
Order By: Relevance
“…Similar results have been demonstrated in other studies such as Krofta et al [22]. These data suggest an improvement in quality of life for all patients.…”
Section: Cure Ratesupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results have been demonstrated in other studies such as Krofta et al [22]. These data suggest an improvement in quality of life for all patients.…”
Section: Cure Ratesupporting
confidence: 91%
“…Therefore, morbidity was essentially the same across groups. Krofta et al [22] reported bladder perforation with 0.7% and 0% of TVT and TOT procedures, respectively. Iatrogenic bladder perforation occurred in 2 patients (3.3%) receiving TVT.…”
Section: Complicationsmentioning
confidence: 99%
“…6 The included studies utilized heterogeneous terms to define pain and pain location (eg, groin pain, thigh pain, wound discomfort, inner thigh discomfort, and groin pain during vaginal palpation). [7][8][9][10][11][12] The largest prospective randomized trial comparing retropubic and transobturator midurethral slings was the Trial of Mid-Urethral Slings. 2 Selfadministered postoperative pain diaries and pain assessments were collected at regular intervals for up to 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Strengths of our study include the large, randomized, prospective, multicenter Trial of MidUrethral Slings database used for this secondary analysis and the use of standardized questionnaires and strictly defined anatomic areas that were described to participants using standardized terminology and body maps at frequent intervals to assess postsurgical pain. The inclusion of the use of any pain medication for pain resulting from the incontinence operation in the definition of absence of surgical pain allowed for a clinically relevant assessment of the resolution of pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, these were not pooled estimates as different studies have used differing criteria for measuring outcome. Analysis of four RCT shows that the objective failure rates for TVT range from 10 to 19% 12,16,19,21 . Although in a study by Porena et al .…”
Section: Tension Free Vaginal Tape (Tvt)mentioning
confidence: 99%